Plasma nitric oxide and leptin values in patients with olanzapine-induced weight gain - Atmaca, Murad; Tezcan, Ertan; Ustundag, Bilal (Pergamon-Elsevier Science Ltd, 2007)
We previously investigated leptin levels in antipsychotic-induced weight gain and found that atypical antipsychotic, especially clozapine and olanzapine-induced weight gain is related to increased levels of leptin. It has been suggested that nitric oxide (NO) is a potential regulator of leptin-induced lipolysis. To explore the pathophysiology of weight gain during atypical antipsychotic treatment, we planned to investigate olanzapine's influence on leptin and NO levels and weight gain. The study comprised 21 patients with schizophrenia who were enrolled in olanzapine monotherapy, and 21 healthy controls. The fasting plasma NO and leptin levels were measured in both patients and controls at baseline. The patients were also evaluated at sixth week according to the Positive and Negative Syndrome Scale (PANSS), body mass index (BMI), weight, serum leptin and NO levels. At baseline, the mean leptin level in the olanzapine group was not different compared. to that in controls after BMI or age adjustment. A significant increase in leptin levels by means of olanzapine use was seen (P < 0.01). Higher plasma NO levels were observed in patients with schizophrenia compared with the control group at baseline (P < 0.01). At the evaluation of week 6, a significant decrease in the mean plasma NO level was found in the olanzapine group (P < 0.05). The changes in total PANSS scores were correlated with change in leptin levels (r = 0.58, P < 0.05), and with the change in weight (r = 0.54, P < 0.05). In addition, there was a severe significant negative correlation between the changes in leptin levels and NO levels (r = 0.73, P < 0.01). The results confirmed that leptin and NO might be associated with olanzapine-induced weight gain. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: olanzapine; leptin; nitric oxide; weight gain